1991
DOI: 10.1136/gut.32.9.1024
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in the Bedouin Arabs of southern Israel: rarity of diagnosis and clinical features.

Abstract: A prospective epidemiological and clinical study of ulcerative colitis and Crohn's disease was undertaken in the Bedouin Arabs of southern Israel between 1981 and 1990. There were six patients with ulcerative colitis and the prevalence rate in 1990 was calculated to be 9-8/105 (95% confidence intervals 3.6-17.4) in the total population, or 6-2/105 (0.8-22.5) in men and 13.7/105 (3.7-35.0) in women. Two cases of Crohn's disease occurred, both in women; the prevalence rate was 3 2/10 (0 4-11-8) Results are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…There was no significant difference in the occurrence of the disease between the Omani and expatriate population. A similar low rate was reported in Bedouin Arabs in southern Israel (prevalence 9.8/100,000) and also in the province of Granada, Spain (incidence 2/100.000/year) [3,15]. In the present study we did not find any significant change in the incidence of UC over the 8-year study period.…”
Section: Discussionsupporting
confidence: 36%
“…There was no significant difference in the occurrence of the disease between the Omani and expatriate population. A similar low rate was reported in Bedouin Arabs in southern Israel (prevalence 9.8/100,000) and also in the province of Granada, Spain (incidence 2/100.000/year) [3,15]. In the present study we did not find any significant change in the incidence of UC over the 8-year study period.…”
Section: Discussionsupporting
confidence: 36%
“…In the Arab population, a growing number of publications have noted an increasing trend [5, 6, 7, 8, 9, 10, 11, 12, 13, 14]. Few reports have been published from the Persian Gulf area [9, 10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports from Indian immigrants in Leicestershire, England [4], Israel [5, 6, 7, 8], Oman [9], Iran [10], Kuwait [11], Turkey [12, 13], Lebanon [14], and South Africa [15]all suggest an increasing incidence. However, UC seems to be uncommon in Singapore [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that it was the stress of relocation which caused the increased risk of developing IBD. However, studies on the same population since have suggested that in fact exposure to new environmental factors such as hygiene or food may be more important [12] . Li et al [13] used retrospective population data to examine whether a stressful life event could predispose to IBD.…”
Section: Stress and The Development Of Ibdmentioning
confidence: 99%